Stage-oriented risk classification in new product development: a systematic literature review - Akram, Muhammad; Pilbeam, Colin; Qazi, Abroon; Al-Mhdawi, M. K. S.; Afzal, Abdul Rahman (MDPI, 2026)
Each of the stages of the New Product Development (NPD) process is vulnerable to different forms of risk. The existing categorizations of these risks are partial, ill-defined, or lack depth. Deploying a systematic literature review methodology, we identify 65 empirical studies that identify sources of risk in NPD. Synthesizing this information, we develop a broad, meaningful, and recognizable taxonomy with five main categories of risk, each with a number of sub-categories. It also takes into consideration the increasingly significant role of sustainability-oriented innovation, including how environmental, technological, and operational risks interact in influencing sustainable performance and resilience in NPD systems. This taxonomy is then used to identify the existing risks inherent in each stage of the NPD process, revealing areas for future research and the applicability of the taxonomy for resolving current issues in NPD risk management theory and practice. Linking the issues of NPD risks with sustainability challenges, this study contributes to innovation management theory and the sustainable development of new products.
This article belongs to the Section Sustainable Management
Keywords: 35 Commerce, Management, Tourism and Services; 33 Built Environment and Design; 3303 Design; 3507 Strategy, Management and Organisational Behaviour; 9 Industry, Innovation and Infrastructure; risk; new product development; taxonomy; systematic literature review; sustainability; sustainable innovation; resilience